Evaluating Mangrove Degradation in Teluk Lembar: A DPSIR-Based Regression Analysis. (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
This study identifies DPSIR (Drivers, Pressures, States, Impacts, Responses) factors affecting mangrove degradation and evaluates the effectiveness of a regression-based DPSIR model in the Teluk Lembar area, West Lombok Regency. A quantitative approach was applied using field surveys and community questionnaires (n = 45) to collect biophysical and socio-economic data. Multiple linear regression was employed to examine how DPSIR pressure variables─rehabilitation frequency, community participation, land clearing, and water quality─affect mangrove biodiversity and density. Land clearing and poor water quality were the most significant predictors of mangrove degradation. The regression model for biodiversity produced R = 0.820 and R² = 0.673, while the model for density yielded R = 0.964 and R² = 0.929 (p < 0.05). These findings indicate that anthropogenic pressures strongly influence both the structural and functional aspects of mangrove ecosystems. The study demonstrates that integrating the DPSIR framework with regression analysis effectively quantifies human-environment interactions driving mangrove degradation. It recommends policy interventions emphasizing continuous mangrove rehabilitation, stricter control of land conversion, and enhanced community participation to ensure the ecological sustainability of mangrove ecosystems in coastal regions.